Design Considerations for Next‐Generation Polymer Sorbents: From Polymer Chemistry to Device Configurations. Issue 16 (1st July 2022) - Ouimet, Jonathan Aubuchon; Xu, Jialing; Flores ‐ Hansen, Carsten; Phillip, William A.; Boudouris, Bryan W.
Abstract: Adsorption‐based separations have the potential to enhance the sustainability of established industrial processes and facilitate the adoption of new practices. They also provide ways to meet emerging needs in the isolation of resources from non‐traditional supplies and the remediation of hazardous environmental contaminants. In this regard, there are significant opportunities to advance both fundamental polymer science and engineering applications through next‐generation adsorbent systems. Here, after briefly reviewing the history, potential application space, and underlying physics of polymer sorbents, design considerations that connect macromolecular design with systems‐level functionality, are discussed. First, polymer processing conditions are discussed in terms of the final nano‐ and microscale structures produced. Subsequently, the macromolecular chemistry of the materials is analyzed with respect to the ability of the separations systems to have analyte‐specific binding. Finally, a similar analysis is performed regarding the desorption mechanism used to release the target solutes. In this way, the manuscript attempts to connect macromolecular architecture with polymer physics and materials processing to provide guidance on how these important interrelationships impact the ultimate performance of sorbent systems. Abstract : Separation processes based on adsorption are critical for the sustainability of many sectors of the chemical enterprise, and they also offer the potential to isolate resources from non‐traditional supplies while potentially remediating environmental contaminants. This review highlights how new polymeric sorbents, and their associated device configurations, could revolutionize this field through selective, stimuli‐responsive, and reusable designs.